الوظيفة الدلاليّة في ضوء مناهج اللسانيات (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
يستعرض هذا البحث " الوظيفة الدلاليّة " للغات بوصفها أهم وسائل الاتصال والتفاهم بين بني البشر، مميّزاً بين دراسة اللغات باعتبارها نظاماً من الرموز الصوتية العرفية الاعتباطية، وبين علم العلامات " Semiologe " بكونه علماً يدرس الرموز والعلامات اللغوية وغير اللغوية، ويعد علم اللغة " Linguistigue " أحد فروعه. كما يُظهر البحث صور المعنى ببساطته وتعدّده، بجلائه وغموضه، بثباته وتحوله، وبقدرة اللغة في هذه الحالات جميعها على أداء وظيفتها بيسر وسهولة، مبيناً بأن الكشف عن " المعنى الدلالي " هو النظر في العلاقة المتبادلة بين الدال والمدلول من خلال أنظمة اللغة ( الصوتية والصرفية والنحوية ) باعتبار كل منها فرعاً من فروع البحث عن المعنى، وما يضاف إلى ذلك من معطيات المعجم والمقام. أما الرموز الأخرى التي لا تتحقق دلالتها من خلال النظام اللغوي؛ فيدرسها علم العلامات العام وما يتفرع عنه من علوم أخرى. ومن الأمور المسلم بها أن النشاط الكلامي ذا الدلالة الكاملة لا يتكوّن من مفردات فحسب، بل يتكون من أحداث كلامية وامتدادات نطقية تكوّن جملاً تتحدّد معالمها بوقفات أو بسكنات أو نحو ذلك؛ فإن علم الدلالة اللساني         " Semantics " لا يقف فقط عند معاني الكلمات المفردة، بل يتعداها إلى دراسة معنى الجملة، وإلى كل شكل لغوي له معنى، وهذا يعني أن يشرح عالم اللغة كيف تحلّل كلّ لغة خبرة الإنسان إلى وحدات حاملة للمعنى. This Research deals with the "Semantic Function" of languages being the most important communication and understanding means among the people. It distinguishes between the study of the languages as a system of random traditional phonetic symbols and Semiology as a science that studies symbols, linguistic and non-linguistic symptoms, of which Linguistics is a branch. The research also shows the figures of the meaning in its simplicity and multiplicity, clarity and ambiguity, stability and changeability, as well as the ability of language in all these cases to perform its function easily and simply. It shows that exhibiting the "semantic meaning" is to look into the mutual relation between the signifier and the signified through the language systems (phonetic, morphological and syntactic), considering each of them one of the branches for searching for meaning, in addition to the data of the dictionary and position. The other symbols, whose indication cannot be revealed through the linguistic system, are studied by General Semiology and its other branches. Speech activity with its full meaning does not consist of vocabulary alone, but of speaking events and pronunciation extensions forming sentences whose features are determined by pauses, holds or the like. The linguistic semantics does not hold at the meanings of the single words, but moves to the study of the sentence meaning, and to every linguistic form having a meaning, i.e. the linguist has to explain how each language analyzes man's experience into units that bear the meaning.